Characterization of a Fabry-Perot Cavity Using a Single-Frequency Laser - DARÉ, João Lucas Romão Gomes (2025)
The present dissertation successfully characterized a low-finesse Fabry-Perot cavity. The cavity was locally constructed and coupled to a commercial single-frequency laser from QPhotonics. We needed to develop an apparatus to stabilize the mechanical vibrations to realize the experiment. We measured a finesse value of 720 ± 16, a photon lifetime of (50 ± 0.03) ns, a mirror reflectance of 0.9966 ± 0.0006, a quality factor of 8.86 × 107, and a cavity’s linewidth of (4.0 ± 0.7) MHz. Estimating a value for the cavity propagation-loss coefficient of (0.017 ± 0.003) m−1 was also possible.